More Information May Reduce Errors for Novice Users: Usability Testing and Redesign of the Square Register App. (September 2014) - Pybus, Lawton; Taub, Michelle; Clark, Hallie; Furlough, Caleb
The popular Square Register app was tested and redesigned for better initial performance using human factors methods. The research team interviewed both current and potential users who expressed concerns and questions about the nature of the app. We conducted further usability tests to evaluate weaknesses in the app interface and to guide redesigns. We created semi-functional prototypes to test the benefits of these design recommendations. Results were mixed, but partially support including additional information in the app for the benefit of novice users. Issues found during prototype use are discussed.